Development of the COVID-19 Real-Time Information System for Preparedness and Epidemic Response (CRISPER), Australia - Field, Emma; Dyda, Amalie; Hewett, Michael; Weng, Haotian; Shi, Jingjing; Curtis, Stephanie; Law, Charlee; McHugh, Lisa; Sheel, Meru; Moore, Jess; Furuya-Kanamori, Luis; Pillai, Priyanka; et al. (Frontiers in Public Health, 2021)
Accurate and current information has been highlighted across the globe as a critical requirement for the COVID-19 pandemic response. To address this need, many interactive dashboards providing a range of different information about COVID-19 have been developed. A similar tool in Australia containing current information about COVID-19 could assist general practitioners and public health responders in their pandemic response efforts. The COVID-19 Real-time Information System for Preparedness and Epidemic Response (CRISPER) has been developed to provide accurate and spatially explicit real-time information for COVID-19 cases, deaths, testing and contact tracing locations in Australia. Developed based on feedback from key users and stakeholders, the system comprises three main components: (1) a data engine; (2) data visualization and interactive mapping tools; and (3) an automated alert system. This system provides integrated data from multiple sources in one platform which optimizes information sharing with public health responders, primary health care practitioners and the general public.